2016
DOI: 10.1080/10538712.2015.1078867
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress and Depression in the Nonoffending Caregivers of Sexually Abused Children: Associations With Parenting Practices

Abstract: Caregiver mental health is a known correlate of parenting practices, and recent research indicated that parental depression following childhood sexual abuse disclosure is associated with concurrent parenting difficulties. The present study extended this line of research by investigating posttraumatic stress symptoms and depression in a sample of caregivers (N=96) of children who experienced sexual abuse recruited from a Children’s Advocacy Center, as well as parenting practices reported by both caregivers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
1
12
1
3
Order By: Relevance
“…Using a rigorous qualitative research methodology, our findings are consistent with prior research showing high levels of distress and common feelings of anger, depression, and guilt among caregivers of sexually abused children (Davies, 1995; Hill, 2001; Jobe-Shields et al, 2016; Kelley, 1990; Lewin & Bergin, 2001; Manion et al, 1996; Mannarino et al, 2007; McCourt et al, 1998; Runyon et al, 2014; Santa-Sosa et al, 2013). The specific sources of distress identified by caregivers in our study are in line with previous research.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Using a rigorous qualitative research methodology, our findings are consistent with prior research showing high levels of distress and common feelings of anger, depression, and guilt among caregivers of sexually abused children (Davies, 1995; Hill, 2001; Jobe-Shields et al, 2016; Kelley, 1990; Lewin & Bergin, 2001; Manion et al, 1996; Mannarino et al, 2007; McCourt et al, 1998; Runyon et al, 2014; Santa-Sosa et al, 2013). The specific sources of distress identified by caregivers in our study are in line with previous research.…”
Section: Discussionsupporting
confidence: 87%
“…Studies have found high levels of distress, posttraumatic stress disorder (PTSD), and depression among caregivers of sexually abused children (Jobe-Shields, Swiecicki, Fritz, Stinnette, & Hanson, 2016; Kelley, 1990; Lewin & Bergin, 2001; Manion et al, 1996; Mannarino, Cohen, Deblinger, & Steer, 2007; Runyon, Spandorfer, & Schroeder, 2014; Santa-Sosa, Steer, Deblinger, & Runyon, 2013). Symptoms of caregiver distress have been shown to be comparable in severity to those of female psychiatric outpatients and persist up to 1 to 2 years after a child’s sexual abuse disclosure (Kelley, 1990; Newberger, Gremy, Waternaux, & Newberger, 1993).…”
mentioning
confidence: 99%
“…A considerable number of mothers with a history of unresolved trauma have also been found to experience comorbid mental health problems, mainly PTSD and depression symptoms or diagnoses (Ammerman, Putnam, Chard, Stevens, & Van Ginkel, 2012;Jobe-Shields, Swiecicki, Fritz, Stinnette, & Hanson, 2016). Clinically speaking, such comorbidity is more often expected in mothers with a CSA history and can be particularly significant when it concerns the mothers of children who have been recently victimized.…”
Section: The Comorbidity Of Ptsd Depression and Dissociation As Indicmentioning
confidence: 99%
“…Following disclosure or discovery that their child has been sexually abused, nonoffending caregivers may experience depression, posttraumatic stress and increases in anxiety [36]. Shields and colleagues found that following child sexual abuse disclosure, 24% of caregivers met diagnostic criteria for depression or PTSD or both [36].…”
Section: Nonoffending Caregiver Individual Therapymentioning
confidence: 99%
“…Following disclosure or discovery that their child has been sexually abused, nonoffending caregivers may experience depression, posttraumatic stress and increases in anxiety [36]. Shields and colleagues found that following child sexual abuse disclosure, 24% of caregivers met diagnostic criteria for depression or PTSD or both [36]. Parental distress was associated with decreases in positive Intervention Strategies for Promoting Recovery and Healing from Child Sexual Abuse DOI: http://dx.doi.org/10.5772/intechopen.97106 parenting and caregiver involvement with the victim.…”
Section: Nonoffending Caregiver Individual Therapymentioning
confidence: 99%